Research New Ways of Processing Polymer Waste that was Formed as a Result of Operation - Shixaliyev Kerem Seyfi (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
In this study, the reasons for the decommissioning of polymer materials are shown and recycling methods are analyzed. Polymer materials do not rot, corrode, etc. if their characteristics are taken into account, their recycling is an economic problem as well as an ecological problem that needs to be solved. Taking into account all this, the methods of obtaining purposeful compositions from some polymer wastes have been studied. its destruction mainly occurs as a result of high temperatures. As a result, the molecular mass of RS (rubber scrub) decreases. When studying this in an oxygenated and non-oxygenated environment, the maximum stability of RS is observed in the temperature interval of 180°C. Therefore, we adopted the temperature of 180°C to modify road oil bitumen with RS waste. The most effective field of use of polymer materials is the modification of road bitumen.